Interpretation Peculiarities of the Sleeping Beauty Motif in D.H. Lawrence`s Short Story “Princess” - Lyudmyla M. Kulakevych (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2021)
The reception of D.H. Lawrence`s works in Western and Ukrainian literary criticism is reflected in detail in Natalia Styrnik`s thesis. She concluded that Lawrence`s short stories remain underexplored in modern Ukrainian literary criticism. The applicant herself undertook to identify the leading themes, motives, and artistic peculiarities of the implementation of the latter. However, the specifics of the female image in the short stories of the English artist lack her attention, there are only occasional characteristics of a particular heroine. The aim of the article is to determine the peculiarities of the interpretation of the Sleeping Beauty Motif in the short story by D.H. Lawrence “The Princess”. The objective is to determine the basis of the plot of the short story and analyze the artistic components of the main character’s image. To achieve our goal, we use the elements of motif, receptive-interpretive psychoanalytic and comparative methods of analysis. What strikes the eye when reading the short story is the popular plot about so beautiful princess that no man in the kingdom is worth even her little toe. It is a typical plot for fairy tales of different nations. The heroine's lineage with the kings is mentioned at the beginning of the short story due to the origin of her father. Traditionally, in fairy tales, the birth of a child is the result of one of the parents’ interactions with the other world. In Lawrence`s story, this is transformed into the unusual behavior of Colin Urquhart, whose attitude to his married life was so unusual that his wife regarded him as an “unreal creature”, “echo”, “ghost”, which is repeatedly emphasized in the text. The girl`s connection to the other world unfolds through the repeatedly articulated motif of the changeling. In fairy tales, the early death of the mother and the introduction of an evil stepmother are determined by the vital need of the girl to grow up independently, because of the kindness of the mother, her excessive care hinders the deeper development of the young woman and her ability to respond to life's problems. It is established that in Lawrence`s short story the motif of the mother's death undergoes transformations: a two-year-old child finds herself under the full care of her father, who raises the girl in a perfectly romantic atmosphere. It is he who instills a behavioral model of a princess in his daughter, unattainable to any man. As the father and daughter reside on the European continent, and the maternal grandparents live in the United States, it creates an illusion that the mother's family and the father's families belong to different “worlds” – different cultures/worldviews. Colin Urquhart, and later his daughter, embodies a romantic culture that tends to idealize a woman as a beautiful lady, and the knight's love for her is perceived as a deep platonic affection. The romantic worldview is manifested through the details of appearance (Urquharts have blue eyes), the style of the heroine’s clothes, her asexuality. The essence of the beautiful heroine is expressed by one of her names – Dollie, which urges us to perceive the living as the inanimate, understand the existence of the Princess as mechanical, devoid of feelings and sensations, alienated from other people`s lives. Her father Colin being presented through the micro images of the bodiless ghost/phantom/echo can also be interpreted as his asexuality on the one hand, while on the other, it can be seen as the mortality/irrelevance of his life principles, which he himself adheres to and instills in the girl. Many fairy tales convey the need to have a family, which is a marker of a socialized person. The search for a marriage partner in a fairy tale always takes place in a space “alien” to the protagonist, which is often defined as “another kingdom”, “distant lands”. According to the fairy-tale canon, to solve the problem, a woman goes on a journey and as a result gets closer to an impoverished but physically fit and silent Mexican, encouraging him to take this dangerous trip to the mountain forests with her. The heroine deliberately leads to the situation where she ends up alone with the man, but later she turns out to be unable to “turn off” the pattern of the princess cultivated by her father and accept the man with his nature. The dream essentially announces the future fate of Dollie – “to be buried alive”, because she makes every effort to defend her existence as a disembodied/asexual being, thus burying a woman within herself. Thus, the heroine`s common sense and instincts could not prevail over the cultural superstructure called “Princess”. According to the fairy-tale canon, even as a young girl, the protagonist showed extraordinary abilities – in the short story her artistic talent and knowledge were repeatedly noticed: the young woman reads the classic literary novels not in translation, but in the original language, which speaks highly of her intelligence. We can assume that not only parental upbringing, but also classical literature, with its taboo on sexual life until the first third of the twentieth century, influenced the heroine. In mind of the Princess two op- ISSN 2523-4463 (print) ВІСНИК УНІВЕРСИТЕТУ ІМЕНІ АЛЬФРЕДА НОБЕЛЯ. ISSN 2523-4749 (online) Серія «ФІЛОЛОГІЧНІ НАУКИ». 2021. № 2 (22) posite images of men are formed: either he was a disembodied companion of a beautiful lady, or “a rough monster”, “Caliban”. The text repeatedly suggests that Mary Henrietta Urquhart could have been quite happy with Domingo Romero, but due to her distorted-romantic view of men, it never happened. The end of the short story is seemingly happy – the heroine is saved, she returns home, to her former life, and even marries a man who, given his age, most likely was not a sexual partner to her but compensated for the deceased father. This conclusion can be explained both by the fact that the “kiss” of the Mexican, which the Princess initiated herself, had not awakened the woman in her, she remains a sleeping beauty forever. D.H. Lawrence`s short story meets the canons of a fairy tale and is read like the modern-day fairy tale showing you how you should not raise a girl.